Strategies for Top-Rated Scientific Journals: Democracy or Closed Ecosystem? - S. V. Orekhova; M. V. Evseeva; E. V. Kislitsyn (Управленческие науки)
Researchers rely on a system of scientometric ratings when they assess the development of a scientific journal. This approach does not allow us to understand the reasons for the results achieved and the specifics of the business model of the publication. The paper describes the study of scientific journals through a prism of the ecosystem approach. The hypothesis is tested that a highly rated scientific journal, its authors and readers together represent a closed ecosystem with specific properties. The research methodology is based on the author’s toolkit which consists on the calculation of ecosystem closeness indicators: the share of affiliated authors, their correlation with the average influence of a paper, diversity and fluidity. The authors suggest that low rates of variability and diversity indicate a closed type of journal ecosystem. Generalization and interpretation of empirical results was carried out by the method of cluster analysis. The information base is a panel metadata of 20 scientific Russian journals for 2013–2020, which have the maximum Science Index ratings on economic and management fields. Also, the authors analyzed the data on the number and level of concentration publications by the editorial board members and staff of the holding institution, as well as the intensity of publications of individual authors. There have been identified four clusters of studied journals being as a base of the empirical verification. The first and third clusters are characterized by the highest rate of closeness. The lowest level of variability in the sample has been recorded for the third cluster. The journals of the second and fourth clusters have a conditionally closed ecosystem and have been characterized by a top-rated of variability. They are characterized by a low share of publications by affiliated authors. However, it was revealed that there had been a group of authors who had a significant impact on the journal’s ecosystem development. The study results can be of value for the strategies formation of scientific journals development.